THE EFFECTIVENESS OF TALKING STICK MODEL ON STUDY LEARNING MATHEMATICS RESULTS STUDENTS FOUR GRADES - rismi vidayanti (PENDAS MAHAKAM: Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2017)
This study aims to determine the effectiveness of the model Talking Stick on the results of learning mathematics fourth grade students SD Negeri Karangsumber 01 Pati regency. The research method used is quantitative descriptive. This type of research is pre experimental with one group pretest-posttest design design .. The data obtained is analyzed by using descriptive analytic technique of kunatitatif. The results showed that there was a significant difference of students' learning achievement after using Talking Stick model before using Talking Stick model (t_hitung = 6,208> t_tabel = 2,074). The average score of student learning outcomes after using the Talking Stick model (71.7) was higher than the average learning outcome before using the Talking Stick model (58.8). It can be concluded that the Talking Stick model is effective on the learning outcomes of fourth grade students of SD Negeri Karangsumber 01 Kabupaten Pati.